A Web-based Music Learning Environment: A Case Study of Users' Experiences - Inkeri Ruokonen; Anu Sepp; Aleksi Ojala; Lenita Hietanen; Vesa Tuisku; Heikki Ruismäki (Cognitive Councelling Research and Conference Services - C-crcs, 2022)
The purpose of the study is to research how music is learned in a web-based learning environment. The users of a web-based learning environment were asked to perform a self-assessment about their music learning. The research question was to determine which kind of learning experiences students had when studying music in a web-based learning environment. The other aim was to discover the students’ main interests in their music studies and the kinds of support they needed for their web-based learning. Finally, the users were asked to suggest some ways to develop a digital learning environment of music. The data was collected by using an equestionnaire that was open for all users who studied on a Finnish web-based music learning environment during one study year. Data from 82 respondents was analysed using content analysis and the results are presented through quantitative tables and figures with qualitative results obtained from the content analyses of answers to open-ended questions. According to the results, most of the users found that the motivation to study music increased during the studies. Preferences of learning methods were individual but most of the respondents hoped web-based learning environment could be developed together with blended learning settings where web based learning and contact lessons could be integrated. The individual support from a web teacher and a peer community were also needed.